2010
DOI: 10.1002/chem.200903282
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of HHeF by Complexation: Is it a Really Viable Strategy?

Abstract: Ab initio calculations at the MP2 and CCSD(T) levels of theory have disclosed the conceivable existence of fluorine-coordinated complexes of HHeF with alkali-metal ions and molecules M(+) (M(+)=Li(+)-Cs(+)), M(+)-OH(2), M(+)-NH(3) (M(+)=Li(+), Na(+)), and MX (M=Li, Na; X=F, Cl, Br). All these ligands L induce a shortening of the H-He distance and a lengthening of the He-F distance accompanied by consistent blue- and redshifts, respectively, of the H-He and He-F stretching modes. These structural effects are qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…Recent calculations predict that complexation with alkali metal cations and various small molecules also does not lead to sufficient stabilization of HHeF. 30 M(I)FHeO (M = Cs, NMe 4 ) described by Grochala are two more candidates for neutral He-containing molecules. 31 These are derivatives of the metastable À FHeO anion, first theorized by Hu et al in 2005.…”
Section: Previous Theoretical Explorationsmentioning
confidence: 99%
“…Recent calculations predict that complexation with alkali metal cations and various small molecules also does not lead to sufficient stabilization of HHeF. 30 M(I)FHeO (M = Cs, NMe 4 ) described by Grochala are two more candidates for neutral He-containing molecules. 31 These are derivatives of the metastable À FHeO anion, first theorized by Hu et al in 2005.…”
Section: Previous Theoretical Explorationsmentioning
confidence: 99%
“…However, so far no stable compound containing helium has been synthesized, except for structures where helium atoms are physically trapped inside fullerene cages 4. One promising type of novel compounds are noble-gas hydrides of the form HNgY where Ng is a noble-gas atom and Y an electronegative fragment 5, 6. A recent review2 lists 23 of these hydrides, but none including helium.…”
Section: Introductionmentioning
confidence: 99%
“…HHeF was initially predicted to be merely metastable 7. It might in fact be stabilized by the environment but has not yet been detected 6, 8…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies using multireference methods have showed that the barrier is even smaller than initially thought, and the predicted lifetime of HHeF is only 157 fs (Takayanagi and Wada 2002). It was also suggested that HHeF cannot be sufficiently well stabilized by complexation (Giordani et al 2010). Some authors considered placing (or in situ generating of) HHeF molecules in the helium matrix and applying high pressure (Bihary et al 2002).…”
mentioning
confidence: 99%